Method for improving high-voltage stability of high-nickel ternary positive electrode material
Through lactic acid-assisted interface engineering technology, H+/Li+ ion exchange and carbon cladding construction are carried out on the surface of high-nickel ternary positive electrode materials, which solves the stability problem during high voltage cycles and significantly improves the cycle stability and electrochemical performance of the battery.
Patent Information
- Application Number
- CN202411801535.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-11
AI Technical Summary
During the 4.5V high-nickel ternary cathode material has problems such as transition metal ion dissolution, severe crystal phase transformation, electrolyte decomposition, and active lithium loss during high voltage cycle, resulting in fast battery capacity decay and poor rate performance.
Through lactic acid assisting interface engineering strategy, H+/Li+ ion exchange reaction is carried out on the surface of high-nickel NCM811 material, residual lithium compounds are eliminated, and carbon cladding is constructed in situ to reduce the dissolution of transition metal ions and mechanical cracks.
It significantly improves the high voltage stability of high-nickel positive electrode materials, reduces polarization, protects the crystal structure, delays gas release, stabilizes the electrode/electrolyte interface, and improves the cycle stability of the battery.
Smart Images

Figure CN119601637A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of energy power battery material preparation, and relates to a method for improving the high voltage stability of high nickel ternary positive electrode materials, and specifically to a method for improving the cycle stability of high nickel ternary positive electrode materials for lithium ion batteries. Background Art
[0002] Lithium-ion batteries are an important source of power for new energy vehicles, grid energy storage, portable electronic devices, and power tools. In recent years, with the rapid development of the new energy industry, the demand for lithium batteries has shown explosive growth, and the market has continuously put forward higher requirements for the energy density of lithium-ion batteries. In terms of battery optimization design, there are two main ways to increase the energy density of batteries. One is to increase the specific capacity of the positive and negative electrode materials of the electrode sheet, and the other is to increase the operating voltage of the battery. Therefore, high nickel NCM811 material (ternary nickel cobalt manganese oxide LiNi x Co y Mn 1-x-y O2, Ni ≥ 80%) has become a hot topic in current research (specific capacity ~ 200mAh / g), but the application of NCM811 still has many problems, especially at 4.5V ( vs. Li / Li + ) During high-voltage cycling, the dissolution of transition metal ions intensifies, causing serious crystal phase changes, and the electrolyte is constantly catalytically decomposed on the surface of the material, resulting in serious electrolyte consumption and continuous loss of active lithium, causing rapid battery capacity decay and poor rate performance. At the same time, in the production process of NCM811 materials, excessive lithium salts are often added to ensure the formation of a highly ordered layered structure, which will cause some lithium to remain on the surface of the material. During long-term storage or battery assembly, the residual lithium tends to react with H2O and CO2 in the environment to form a surface layer composed of Li2CO3 and LiOH. The residual lithium compounds generated will cause the material to produce a large amount of gas during the charge and discharge cycle, thereby threatening the safety performance of the battery.
[0003] At present, the measures to improve the performance of lithium-ion batteries using the NCM811 series as the positive electrode are mainly divided into two categories. One is to coat the surface of the positive electrode material and dope the bulk phase to improve the stability of the positive electrode, and the other is to use electrolyte additives to improve the stability and film-forming properties of the electrolyte. Generally, film-forming additives will decompose on the electrode surface before the main electrolyte solvent to form a layer of solid electrolyte film, thereby inhibiting the decomposition of the electrolyte and protecting the motor from HF corrosion generated by the electrolyte. The surface coating strategy can eliminate residual lithium compounds on the surface of the NCM811 material while constructing a carbon coating layer in situ. This modification strategy can significantly inhibit irreversible phase changes, prevent mechanical cracks inside the particles and slow down gas release, effectively stabilize the electrode / electrolyte interface, and thus improve the high-voltage cycle stability of the NCM811 positive electrode material.
[0004] The present invention provides a method for improving the cycle stability of high nickel ternary cathode materials for lithium-ion batteries. The present invention uses lactic acid to assist the interface engineering strategy. + / Li + The ion exchange reaction builds a carbon coating in situ on the surface of the nickel-rich NCM811 material, while eliminating residual lithium compounds. The carbon coating can significantly reduce the polarization of the Li / NCM811 battery, reduce the dissolution of transition metal ions in the bulk phase of the NCM811 electrode material to a certain extent, protect the crystal structure of the positive electrode from damage, prevent mechanical cracks inside the particles and slow down gas release, effectively stabilize the electrode / electrolyte interface, and make the nickel-rich Li / NCM 811 battery at 4.5V (vs. Li / Li + ) The high voltage cycle stability has been greatly improved, which has important application value for regulating the structure and composition of NCM811 materials to improve their electrochemical properties. Summary of the invention
[0005] In order to solve the problem of poor stability caused by the dissolution of transition metal ions in the bulk phase of high-nickel NCM811 electrode materials, the present invention aims to provide a method for improving the high-voltage stability of high-nickel ternary positive electrode materials.
[0006] Another object of the present invention is to provide a product prepared by the above method.
[0007] Another object of the present invention is to provide applications of the above product.
[0008] The object of the present invention is achieved by the following scheme: a method for improving the high voltage stability of high nickel ternary positive electrode materials, the method uses high nickel NCM811 as the positive electrode material, disperses the NCM811 positive electrode material in a lactic acid / water mixed solution and stirs it, and uses the H generated by lactic acid hydrolysis to +ions, and Li in the residual lithium compound (Li2CO3 / LiOH) on the surface of NCM811 + Ions carry H + / Li + The method comprises the following steps: an ion exchange reaction is performed, and a lactic acid layer is in situ constructed on the surface of the material, and then carbonized at high temperature to obtain a carbon-coated NCM811 positive electrode material with low surface residual lithium compounds, which reduces the dissolution of transition metal ions in the bulk phase of the NCM811 electrode material to a certain extent, protects the crystal structure of the positive electrode from being destroyed, and improves the high voltage stability of the high nickel positive electrode material. The first step is the preparation of high nickel NCM811 material: metal nickel salt, cobalt salt and manganese salt are added into deionized water in a molar ratio of n (Ni): n (Co): n (Mn) = 0.8: 0.1: 0.1, ultrasonic stirring is performed to fully dissolve them, then ammonia solution is added, the pH value is adjusted to 11.3, heated to 65-85 ° C, stirred for 15-24 h, filtered, and the residue is dried at 80-90 ° C to obtain the precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2. Then the precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 and lithium source were mixed in a mass ratio of 1:1.06, ground for 30 min, and placed in a tube furnace. The air in the furnace was first expelled with N2, and then oxygen O2 was introduced. The mixture was kept at 500°C for 6 h, then heated to 750°C and calcined for 15 h. After cooling, high-nickel NCM811 material was obtained. The second step is to improve the high-nickel NCM811 material with the help of lactic acid: weigh a certain mass of the NCM811 material prepared in the first step, add it to 150 ml of lactic acid aqueous solution, mix and stir for 4 hours, then centrifuge and wash repeatedly with deionized water and ethanol until neutral. Dry at 85 °C for 16 hours to obtain a dry powder. Then place the lactic acid-treated NCM811 material in an argon Ar environment, calcine at a suitable temperature for 3 hours, and cool to obtain the modified NCM811 material; The third step is the preparation of electrode sheets: the modified NCM811 powder material, polyvinylidene fluoride (PVDF) and acetylene black are weighed and mixed in a mortar in a mass ratio of 9:0.5:0.5, and then an appropriate amount of N-methylpyrrolidone (NMP) is added as a solvent and aluminum foil is used as a current collector for coating. After drying, the electrode sheets of suitable size are cut out with a cutting machine, and then compacted with a roller press to obtain the positive electrode sheets. Finally, graphite is used as the negative electrode, and a 2325 separator is used to assemble the soft-pack battery and conduct electrochemical performance tests.
[0009] The volume ratio of the lactic acid aqueous solution is controlled to be lactic acid: water = 2:1; The suitable calcination temperature in the improvement of the high nickel NCM811 material is to calcine at 550°C.
[0010] The present invention also provides a lactic acid-modified high-nickel ternary positive electrode material obtained according to the above method.
[0011] The present invention also provides the application of the above product, which is applied to the field of high-performance power lithium batteries.
[0012] The technical principle of the present invention is to use the above preparation process to produce H + The ions will react with the Li2CO3 / LiOH on the surface of NCM811. + Ions carry H + / Li + Ion exchange, and at the same time, a lactic acid layer is constructed in situ on the surface of the material, which is then carbonized at high temperature to obtain a carbon-coated NCM811 positive electrode material with low surface residual lithium compounds. Since the lactic acid / water mixed solution is weakly acidic, the aqueous solution treatment will not damage the layered structure and spherical morphology of the NCM811 material. At the same time, the carbon layer material is an in-situ constructed amorphous carbon, which can significantly reduce the polarization of the Li / NCM811 battery, and to a certain extent reduce the dissolution of transition metal ions in the bulk phase of the NCM811 electrode material, protect the crystal structure of the positive electrode from damage, inhibit irreversible phase changes, prevent mechanical cracks inside the particles and slow down gas release, effectively stabilize the electrode / electrolyte interface, and make the nickel-rich Li / NCM 811 battery at 4.5V (vs. Li / Li + ) The high voltage cycle stability has been greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a transmission electron microscope image of the carbon-coated high-nickel NCM811 positive electrode material obtained in Example 1.
[0014] As can be seen from the figure, the NCM811 material is in the form of particles, and its surface is covered with a thin layer of uniform amorphous carbon material with a thickness of about 8 μm; the carbon layer material is tightly attached to the surface of the NCM811 particles, and the introduction of the carbon layer reduces the dissolution of transition metal ions in the bulk phase of the NCM811 electrode material.
[0015] Figure 2 This is a battery cycle stability spectrum of the carbon-coated high-nickel NCM811 positive electrode material and the high-nickel NCM811 positive electrode material obtained in Example 1.
[0016] The carbon-coated modified NCM811 / graphite full battery can still maintain an ultra-high capacity of 81.5% after 500 cycles at 1 C, while the cyclic stability of the unmodified NCM811 material can only maintain 65.3% of the capacity after 500 cycles at 1 C. It can be seen that the H+ ions produced by lactic acid hydrolysis can exchange the Li+ ions on the surface of NCM811, and the carbon coating of low surface residual lithium compounds can reduce the dissolution of transition metal ions in the bulk phase of the NCM811 electrode material, protect the crystal structure of the material from damage, and thus improve the high voltage stability of the high nickel positive electrode material. DETAILED DESCRIPTION
[0017] This embodiment is implemented on the premise of the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0018] Embodiment 1: A method for improving the high voltage stability of a high nickel ternary cathode material, using high nickel NCM811 as a cathode material, dispersing the NCM811 cathode material in a lactic acid / water mixed solution and stirring the solution, and using the H generated by lactic acid hydrolysis to + ions, and Li in the residual lithium compound (Li2CO3 / LiOH) on the surface of NCM811 + Ions carry H + / Li + Ion exchange reaction, at the same time, a lactic acid layer is constructed in situ on the surface of the material, and then carbonized at high temperature to obtain a carbon-coated NCM811 positive electrode material with low surface residual lithium compounds, so as to reduce the dissolution of transition metal ions in the bulk phase of the NCM811 electrode material, protect the crystal structure of the positive electrode from being destroyed, and improve the high voltage stability of the positive electrode material, according to the following steps: The first step is the preparation of high nickel NCM811 material: Metal nickel salt, cobalt salt and manganese salt were added into deionized water at a molar ratio of n (Ni): n (Co): n (Mn) = 0.8: 0.1: 0.1, ultrasonically stirred to fully dissolve, and then ammonia solution was added to adjust the pH value to 11.3, heated to 80 ° C, stirred for 24 h, filtered, and the residue was dried at 80 ° C to obtain the precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2; the precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 and lithium source LiOH·H2O were mixed and ground in a mass ratio of 1:1.06 for 30 min and then placed in a tube furnace. The air was evacuated with N2, and then oxygen O2 was introduced. The mixture was calcined at 500°C for 6 h, then heated to 750°C and calcined for another 15 h. After cooling, high-nickel NCM811 material was obtained. The second step is to use lactic acid to assist in the improvement of high nickel NCM811 materials: Weigh 2 g of the NCM811 material prepared in the first step, add it to 150 ml of lactic acid aqueous solution, the volume ratio of lactic acid to water is 2:1, mix and stir thoroughly for 4 hours, centrifuge, and repeatedly wash with deionized water and ethanol until neutral; dry at 85 °C for 16 hours to obtain dry lactic acid-treated NCM811 powder; place the lactic acid-treated NCM811 powder in an argon environment, calcine at 550 °C for 3 hours, and obtain the modified NCM811 material after cooling; Then repeat this step several times to obtain a sufficient amount of modified material.
[0019] Step 3: Preparation of electrode sheets: The obtained modified NCM811 material, polyvinylidene fluoride (PVDF) and acetylene black were weighed and mixed in a mortar in a mass ratio of 9:0.5:0.5, and N-methylpyrrolidone (NMP) was used as the solvent and aluminum foil was used as the current collector for coating; after drying, the electrode pieces of suitable size were cut out with a cutting machine, and then compacted with a roller press to obtain the positive electrode pieces; finally, graphite was used as the negative electrode, and 2325 separator was used for the assembly of soft-pack batteries and the electrochemical performance tests were carried out.
[0020] Figure 1 This is a transmission electron microscope image of the carbon-coated modified high-nickel NCM811 material obtained in Example 1. It can be seen from the figure that the NCM811 material is in a granular form, and a thin layer of uniform amorphous carbon material is covered on its surface with a thickness of about 8 μm; the carbon layer material is tightly attached to the surface of the NCM811 particles, and the introduction of the carbon layer reduces the dissolution of transition metal ions in the bulk phase of the NCM811 electrode material.
[0021] Figure 2 Figure 2 is the cycling performance diagram of carbon-coated modified NCM811 / graphite and NCM811 / graphite full battery at 1 C. The carbon-coated modified NCM811 / graphite full battery can still maintain an ultra-high capacity of 81.5% after 500 cycles at 1 C, while the cycling stability of the unmodified NCM811 material can only maintain 65.3% of the capacity after 500 cycles at 1 C. It can be seen that the H generated by lactic acid hydrolysis can effectively improve the cycling stability of the battery. + Ions can exchange Li on the surface of NCM811 + ions, and the carbon coating of low surface residual lithium compounds can reduce the dissolution of transition metal ions in the bulk phase of NCM811 electrode materials, protect the crystal structure of the material from destruction, and thus improve the high voltage stability of high nickel positive electrode materials.
[0022] Embodiment 2: A method for improving the high voltage stability of a high nickel ternary positive electrode material is similar to Example 1 and is implemented by the following steps: The first step is the preparation of high nickel NCM811 material, which is consistent with Example 1; The second step is to improve the high-nickel NCM811 material with the assistance of lactic acid: this step is also similar to Example 1, except that 1.0 g of the prepared NCM811 material is weighed and added to 150 ml of a lactic acid aqueous solution, with a volume ratio of lactic acid to water of 2:1. After being fully mixed and stirred for 4 hours, the mixture is centrifuged and repeatedly washed with deionized water and ethanol until neutral; dried at 85°C for 16 hours to obtain a dry lactic acid-treated NCM811 powder material; the lactic acid-treated NCM811 material is placed in an argon Ar environment, calcined at 550°C for 3 hours, and the modified NCM811 material is obtained after cooling; Then repeat this step several times to obtain a sufficient amount of modified material.
[0023] The third step is the preparation of the electrode sheet. This step is also consistent with Example 1, and the battery is assembled and the electrochemical performance is tested.
[0024] Tests show that the battery material still has good high-voltage stability.
[0025] Embodiment 3: A method for improving the high voltage stability of a high nickel ternary positive electrode material is similar to Example 1 and is implemented by the following steps: The first step is the preparation of high nickel NCM811 material, which is consistent with Example 1; The second step is to improve the high-nickel NCM811 material with lactic acid: This step is also similar to implementation case 1, with the main difference being that 4.0 g of the prepared NCM811 material is weighed and added to 150 ml of lactic acid aqueous solution (lactic acid: water volume ratio is 2:1), fully mixed and stirred for 4 hours, then centrifuged and repeatedly washed with deionized water and ethanol until neutral. Dry at 85 °C for 16 hours to obtain a dry powder. The lactic acid-treated NCM811 material is placed in an argon Ar environment and calcined at 550 °C for 3 hours. After cooling, the modified NCM811 material is obtained. Then repeat this step several times to obtain a sufficient amount of modified material.
[0026] The third step is the preparation of the electrode sheet, which is also the same as in Example 1, and the battery is assembled and the electrochemical performance test is performed. The test shows that the battery material still has good high voltage stability.
[0027] Embodiment 4: A method for improving the high voltage stability of a high nickel ternary positive electrode material is similar to Example 1, and the specific implementation steps are as follows: The first step is the preparation of high nickel NCM811 material, which is consistent with Example 1; The second step is to use lactic acid to assist the improvement of high-nickel NCM811 materials: This step is also similar to Implementation Case 1, with the main difference being that 6.0 g of the prepared NCM811 material is weighed and added to 150 ml of a lactic acid aqueous solution (lactic acid: water volume ratio is 2:1), fully mixed and stirred for 4 h, then centrifuged and repeatedly washed with deionized water and ethanol until neutral. Dry at 85 °C for 16 h to obtain a dry powder. The lactic acid-treated NCM811 material is placed in an argon Ar environment and calcined at 550 °C for 3 h. After cooling, the modified NCM811 material is obtained. Then repeat this step several times to obtain a sufficient amount of modified material; The third step is the preparation of the electrode sheet, which is also the same as in Example 1, and the battery is assembled and the electrochemical performance test is performed. The test shows that the battery material still has good high voltage stability.
[0028] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for improving the high voltage stability of a high nickel ternary cathode material, characterized in that: High nickel NCM811 was used as the positive electrode material. The NCM811 positive electrode material was dispersed in a lactic acid / water mixed solution and stirred. The H generated by lactic acid hydrolysis was + ions, and Li in the residual lithium compound (Li2CO3 / LiOH) on the surface of NCM811 + Ions carry H + / Li + The ion exchange reaction is carried out, and a lactic acid layer is in situ constructed on the surface of the material, and then a carbon-coated NCM811 positive electrode material with low surface residual lithium compounds is obtained by high-temperature carbonization to reduce the dissolution of transition metal ions in the bulk phase of the NCM811 electrode material, protect the crystal structure of the positive electrode from being destroyed, and improve the high voltage stability of the positive electrode material, including the following steps: The first step is the preparation of high nickel NCM811 material: Metal nickel salt, cobalt salt and manganese salt were added into deionized water at a molar ratio of n (Ni): n (Co): n (Mn) = 0.8: 0.1: 0.1, ultrasonically stirred to fully dissolve, and then ammonia solution was added to adjust the pH value to 11.3, heated to 65-85 ° C, stirred for 15-24 h, filtered, and the residue was dried at 80-90 ° C to obtain the precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2; the precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 and lithium source were mixed and ground in a mass ratio of 1:1.06 for 30 minutes and then placed in a tube furnace. The air was first evacuated with N2, and then oxygen O2 was introduced. The mixture was calcined at 500°C for 6 hours, then heated to 750°C and calcined for another 15 hours. After cooling, high-nickel NCM811 material was obtained. The second step is to use lactic acid to assist in the improvement of high nickel NCM811 materials: The NCM811 material prepared in the first step was weighed, added to 150 ml of lactic acid aqueous solution, fully mixed and stirred for 4 hours, centrifuged, and repeatedly washed with deionized water and ethanol until neutral; dried at 85 °C for 16 hours to obtain dry lactic acid-treated NCM811 powder; the lactic acid-treated NCM811 powder was placed in an argon Ar environment, calcined for 3 hours, and cooled to obtain the modified NCM811 material; Step 3: Preparation of electrode sheets: The obtained modified NCM811 material, polyvinylidene fluoride (PVDF) and acetylene black were weighed and mixed in a mortar in a mass ratio of 9:0.5:0.5, and then an appropriate amount of N-methylpyrrolidone (NMP) was added as a solvent and aluminum foil was used as a current collector for coating; after drying, a cutting machine was used to cut out the pole pieces of suitable size, and then a roller press was used to compact them to obtain the positive pole pieces; graphite was used as the negative electrode, and 2325 separator was used for the assembly of soft-pack batteries.
2. The method for improving the high voltage stability of high nickel ternary positive electrode materials according to claim 1, characterized in that: The volume ratio of the lactic acid aqueous solution is controlled to be lactic acid: water = 2:
1.
3. The method for improving the high voltage stability of high nickel ternary cathode materials according to claim 1, characterized in that: The suitable calcination temperature in the improvement of the high nickel NCM811 material is to calcine at 550°C.
4. The method for improving the high voltage stability of a high nickel ternary cathode material according to any one of claims 1 to 3, characterized in that: Follow these steps: The first step is the preparation of high nickel NCM811 material: Metal nickel salt, cobalt salt and manganese salt were added into deionized water at a molar ratio of n (Ni): n (Co): n (Mn) = 0.8: 0.1: 0.1, ultrasonically stirred to fully dissolve, and then ammonia solution was added to adjust the pH value to 11.3, heated to 80 ° C, stirred for 24 hours, filtered, and the residue was dried at 80 ° C to obtain the precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2; the precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 and lithium source LiOH·H2O were mixed and ground in a mass ratio of 1:1.06 for 30 min and then placed in a tube furnace. The air was evacuated with N2, and then oxygen O2 was introduced. The mixture was calcined at 500°C for 6 h, then heated to 750°C and calcined for another 15 h. After cooling, high-nickel NCM811 material was obtained. The second step is to use lactic acid to assist in the improvement of high nickel NCM811 materials: Weigh 2 g of the NCM811 material prepared in the first step, add it to 150 ml of lactic acid aqueous solution, the volume ratio of lactic acid to water is 2:1, mix and stir thoroughly for 4 hours, centrifuge, and repeatedly wash with deionized water and ethanol until neutral; dry at 85 °C for 16 hours to obtain dry lactic acid-treated NCM811 powder; place the lactic acid-treated NCM811 powder in an argon environment, calcine at 550 °C for 3 hours, and obtain the modified NCM811 material after cooling; Then repeat this step several times to obtain a sufficient amount of modified material.
5. The method for improving the high voltage stability of high nickel ternary positive electrode materials according to claim 4, characterized in that: In the second step, lactic acid assists the improvement of high-nickel NCM811 material: this step is also similar to Example 1, the main difference is that 1.0 g of the prepared NCM811 material is weighed and added to 150 ml of lactic acid aqueous solution, the volume ratio of lactic acid: water is 2:1, after being fully mixed and stirred for 4 hours, centrifuged, and repeatedly washed with deionized water and ethanol until neutral; dried at 85°C for 16 hours to obtain a dry lactic acid-treated NCM811 powder material; the lactic acid-treated NCM811 material is placed in an argon Ar environment, calcined at 550°C for 3 hours, and the modified NCM811 material is obtained after cooling; Then repeat this step several times to obtain a sufficient amount of modified material.
6. The method for improving the high voltage stability of high nickel ternary cathode materials according to claim 4, characterized in that: In the second step, lactic acid assists the improvement of high-nickel NCM811 material: This step is also similar to Implementation Case 1, the main difference is that 4.0 g of the prepared NCM811 material is weighed and added to 150 ml of lactic acid aqueous solution (lactic acid: water volume ratio is 2:1), fully mixed and stirred for 4 hours, then centrifuged and repeatedly washed with deionized water and ethanol until neutral. Dry at 85 ° C for 16 hours to obtain a dry powder. The lactic acid-treated NCM811 material is placed in an argon Ar environment and calcined at 550 ° C for 3 hours. After cooling, the modified NCM811 material is obtained. Then repeat this step several times to obtain a sufficient amount of modified material.
7. The method for improving the high voltage stability of high nickel ternary cathode materials according to claim 4, characterized in that: In the second step, lactic acid assists the improvement of high-nickel NCM811 material: This step is also similar to Implementation Case 1, the main difference is that 6.0 g of the prepared NCM811 material is weighed and added to 150 ml of lactic acid aqueous solution (lactic acid: water volume ratio is 2:1), fully mixed and stirred for 4 hours, then centrifuged and repeatedly washed with deionized water and ethanol until neutral. Dry at 85 ° C for 16 hours to obtain a dry powder. The lactic acid-treated NCM811 material is placed in an argon Ar environment and calcined at 550 ° C for 3 hours. After cooling, the modified NCM811 material is obtained. Then repeat this step several times to obtain a sufficient amount of modified material.
8. A lactic acid modified high-nickel NCM811 material obtained according to the method according to any one of claims 1 to 7.
9. An application of the lactic acid modified high-nickel ternary positive electrode material according to 8 in a high-performance power lithium battery.